IOGURTE SABOR BETERRABA (Beta vulgaris L. var. rubra): COMPOSIÇÃO CENTESIMAL, DETERMINAÇÃO DE VIDA ÚTIL E AVALIAÇÃO SENSORIAL - Moraes, Silvana Medeiros (2020)
Beet (Beta vulgaris L. var. rubra) is one of the most cultivated vegetables in Brazil. It is a source of vitamins, minerals and is one of the richest and most accessible sources of betalains, nitrogenous pigments responsible for its purple color and antio